'BIG DATA', THE 'INTERNET OF THINGS' AND THE 'INTERNET OF SIGNS'. Issue 1 (26th March 2013) - O'Leary, Daniel E.
SUMMARY This paper examines the relationship between so‐called 'Big Data', the 'Internet of Things' (the 'Internet of People and Things, ' and the 'Internet of Everything'), and the 'Internet of Signs.' In particular, we investigate how the 'things' in the 'Internet of Things' generate 'Big Data', and how both are used to generate semiotic 'signs'. In addition, we analyse the importance of context in and the relationships between 'Big Data', the 'Internet of Things', and the 'Internet of Signs'. Copyright © 2013 John Wiley & Sons, Ltd.